2011
DOI: 10.1371/journal.pone.0024594
|View full text |Cite
|
Sign up to set email alerts
|

The Composite Effect of Transgenic Plant Volatiles for Acquired Immunity to Herbivory Caused by Inter-Plant Communications

Abstract: A blend of volatile organic compounds (VOCs) emitted from plants induced by herbivory enables the priming of defensive responses in neighboring plants. These effects may provide insights useful for pest control achieved with transgenic-plant-emitted volatiles. We therefore investigated, under both laboratory and greenhouse conditions, the priming of defense responses in plants (lima bean and corn) by exposing them to transgenic-plant-volatiles (VOCos) including (E)-β-ocimene, emitted from transgenic tobacco pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 31 publications
4
43
0
1
Order By: Relevance
“…15 Moreover, (E)-β-ocimene produced by transgenic plants (lima bean and corn) induced priming responses of other plants, successfully attracting predators and parasitoids. 16 In addition, β-ocimene induced the increase of methyl jasmonate and transcript levels of defense/stress-inducible genes in tissue levels in Arabidopsis thaliana DMNT (15) was produced in high amounts by yerba mate plants after both treatments of herbivory (TC and HB). DMNT and 4,8,12-trimethyltrideca-1,3,7,11-tetraene (TMTT) are degradation products of the terpenoids nerolidol and geranlyl-linalool.…”
Section: Discussionmentioning
confidence: 98%
“…15 Moreover, (E)-β-ocimene produced by transgenic plants (lima bean and corn) induced priming responses of other plants, successfully attracting predators and parasitoids. 16 In addition, β-ocimene induced the increase of methyl jasmonate and transcript levels of defense/stress-inducible genes in tissue levels in Arabidopsis thaliana DMNT (15) was produced in high amounts by yerba mate plants after both treatments of herbivory (TC and HB). DMNT and 4,8,12-trimethyltrideca-1,3,7,11-tetraene (TMTT) are degradation products of the terpenoids nerolidol and geranlyl-linalool.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, (E)-DMNT and TMTT have also been reported to function as airborne cues that attract predatory mites (de Boer et al 2004;Kappers et al 2005), which may explain our previously reported findings that infested, second receiver plants that had been placed near infested VOCos-receiver plants were more attractive to P. persimilis in comparison to those that had been placed near the infested VOCwt-receiver plants (Muroi et al 2011). …”
mentioning
confidence: 74%
“…This was likely to have been caused by higher levels of VOCs, including methyl salicylate and (E)-DMNT, its isomer [(Z)-DMNT], and TMTT, released from VOCos-receiver bean plants following infestation of T. uriticae, compared to the T. urticae-infested VOCwt-receiver plants (Muroi et al 2011). As (E)-DMNT and TMTT, emitted as mite-induced lima bean leaf volatiles, are known to play a major role in the communication between damaged and undamaged leaves (Arimura et al 2000), the higher levels of those two VOCs from VOCos-receiver plants could…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations